Youth (ILO GenevaCH, 1986)
Reviews problems and issues confronting young people with emphasis on their demographic and socio-economic situation, their access to education, training and productive employment. Reviews ILO training and employment activities designed to benefit young people. Makes suggestions for future action. Discusses education, training and employment of young people in developing and industrialized countries.
Report v